Implementation of D'volleyball learning application in junior high schools to improve student’s learning outcomes - Destriani, Destriani; Destriana, Destriana; Victorian, Ahmad Richard; Solahuddin, Soleh; Alfarandi, Reza (Journal of Science and Education (JSE), 2023)
This research aims to determine the results of implementing the learning media D'Volleyball Learning Application to improve student's learning outcomes in junior high schools. This research uses an action research method consisting of two cycles. The action takes the form of volleyball learning using the D'volleyball learning application media. The sample in this research was 31 students at State Junior High School 1 Tanjung Batu class VIII, consisting of 11 male students and 20 female students. Data was obtained by conducting pre-cycle and post-tests after each cycle test to determine the level of completeness of students' learning outcomes in volleyball game bottom serve learning material. A significant spike in improvement was seen in the three aspects assessed after being given action in the 2nd cycle. Students' knowledge was improved at 29.23% after cycle 1 and 83.87 after cycle 2, skills were improved at 32.25% after cycle 1 and 83.87 after cycle 2, and attitude were improved at 61.29% after cycle 1 and 80.65% after cycle 2. The implementation of D'Volleyball Learning Application media in learning has been proven effective for use in the learning process at State Junior High School 1 Tanjung Batu.